Dose terapêutica e farmacocinética do tramadol em caprinos submetidos à orquiectomia - Nunes, Talyta Lins (Universidade Federal Rural do Semi-Árido, 2013)
This study aimed to determine the therapeutic dose of tramadol in goats submitted to orchiectomy and to verify the pharmacokinetic parameters of the opioid in the species. Nineteen healthy adult goats were divided into three groups: Group 2 mg, where animals received tramadol at a dose of 2 mg.kg-1; Group 4 mg, where animals received 4 mg.kg-1 of the opioid; and Control Group which received NaCl solution at 0.9%, intravenously. After the treatment administration, lidocaine local infiltration was performed and the animals were subjected to orchiectomy. Heart and respiratory rate, blood pressure and temperature were measured besides the assessment of analgesia. At any sign of pain, ketoprofen was administered. At each time point, venous blood was collected for determination of tramadol pharmacokinetics, by HPLC means. It was observed that 4 mg.kg-1 provided better and longer-lasting analgesia when compared to the other study groups. The animals that received that dose had the smallest values of the vital parameters and, in 66,6% of them, rescue medication was administered only 16 hours after treatment. As for the pharmacokinetics, there was no difference among groups. The highest plasma concentrations of tramadol were 830 and 1479 ng.ml-1 for the animals receiving the lowest and highest doses of the opioid, Half-life was 0.28 ± 0.21 and 0.34 ± 0.24 hours for tramadol in doses of 2 and 4 mg.kg-1 , respectively. There was a wide distribution and affinity to the opioid by all tissues. Tramadol at a dose of 4 mg.kg-1 demonstrated analgesic activity more satisfying and longer lasting associated with absence of side effects in goats undergoing orchiectomy
Clinical effects and pharmacokinetics different doses of tramadol in goats submitted to orchiectomy
Keywords: Goats; Analgesia; Small ruminants; Caprinos; Analgesia; Pequenos Ruminantes; CIENCIAS AGRARIAS::MEDICINA VETERINARIA